Estudio químico bromatológico de diferentes individuos de Eugenia stipitata Mc Vaugh (Arazá) - Barrantes Inga, Ricardo (2002)
The fruit of Eugenia stipitata Mc Vaugh (Arazá) can be used as important source of nutrients. Four fruits of different samples of Arazá show considerable variation of nutrients, especially thiamin, riboflavin, calcium, kalium, magnesium and the variation in low proportion of protein, fat and fiber.